A SYSTEMATIC REVIEW OF USING AUGMENTED REALITY IN TOURISM BETWEEN 2017 AND 2021 (ResearchJet Journal of Analysis and Inventions, 2022)
Technology has transformed the way individuals perceive and apply information and has become an essential part of today's world. Augmented reality technology may overlay interactive real-world items with a layer of virtual elements, such as pictures, text, video, and sounds, in real-time and 3D. Augmented reality allows for seamless transitions between real and virtual worlds. Because of its capacity to bridge the gap and overcome most tourism experience limits, augmented reality technology has attracted much interest in the tourism industry. Over the last years, the fast spread of Augmented Reality (AR) technologies has provided new possibilities and potential to enhance tourism activities. This study presents the results of a systematic review of the literature on augmented reality in tourism. We systematically reviewed all AR articles, including user studies published between 2017 and 2021. A total of 60 papers were reviewed and classified based on a variety of criteria, including the study's environment, research type, augmented reality type, contributing countries where the study took place, author country, augmented reality display systems, research directions, and the majority of study requirements and recommendations. The review's main contribution is to show how augmented reality has been used in the tourism industry and what characteristics each study has. We also pay attention to the restrictions that researchers encounter and future visions for overcoming these constraints. The methods of the review and the classifications of AR research that have arisen in the field of tourism are described in this poster. In addition, the paper discusses trends.